The Influence of Entrepreneurship Education, Entrepreneurial Experience, and Entrepreneurial Motivation on Urban Farming Business Management - Azis, Muhammad; Hasan, Muhammad; Azis, Fajriani; Arisah, Nur; Kemalasari, Andi Anggi (Cita konsultindo, 2025)
The study aims to determine how the relationship between entrepreneurship education, entrepreneurial experience, and entrepreneurial motivation can influence the management of urban farming businesses, especially in the Citra Women Farmers Group located at BTN Citra Tello Permai, Tello Baru Village, Panakkukang District, Makassar City. The sample used in the study was 120 members of the Citra women farmers group. Data analysis used was path analysis using several software for data processing such as Microsoft Excel 2010, SPSS (Statistical Product and Service Solution) version 20.0, and Partial Least Squares (PLS) techniques using SmartPls (version 4.0). The results of the study indicate that in this study: (1) the entrepreneurship education variable has a positive and significant effect on the management of urban farming businesses, especially in the Citra Women Farmers Group; (2) the entrepreneurial experience variable has a positive and significant effect on the management of urban farming businesses, especially in the Citra Women Farmers Group; (3) the entrepreneurial motivation variable has a positive and significant influence on the management of urban farming businesses, especially in KWT Citra; (4) entrepreneurial education, entrepreneurial experience, and entrepreneurial motivation have an influence on the management of urban farming businesses in KWT Citra.